Representasi Penyandang Disabilitas dalam Konten Viral di Palembang: Analisis Wacana Kritis Model Sara Mills - Effendi, Darwin; Nastiti Wulandari, Tri; Rahmadani, Icha; Desyuti Sirait, Putri; Larasati, Gendis; Safera, Dina; Putri Permata, Deva; Zelfi Oktara, Anugrah; Adies Rosanti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The development of social media in the digital era has given rise to a variety of viral content that not only serves as a means of entertainment but also plays a role in shaping public perceptions of certain groups, including people with disabilities. This study aims to examine the representation of people with disabilities in viral content in Palembang using Sara Mills' Critical Discourse Analysis approach. The study used a qualitative descriptive method with documentation techniques for viral content on TikTok and Instagram featuring people with disabilities and their representations. Data were analyzed based on verbal, visual, audio, and performative elements within the videos. The results show that content creators occupy a subject position controlling the narrative, while people with disabilities tend to be positioned as objects through stereotypical representations of entertainment, pity, and pseudo-inspiration. Furthermore, viewers are guided to provide emotional responses through elements of humor and entertainment built into the content. The findings of this study indicate that social media not only represents social reality but also reproduces ideologies and stigmas against people with disabilities through digital discourse practices in society.